Study of Implementation of Good Manufacturing Practices (GMP) in CV “XYZ” - Alfiya Dewi Novanda; Jariyah; Achmad Wahyu Hidayat (Nusantara Science and Technology Proceedings, 2022)
Food safety is one of the important factors in the implementation of the food system that must be followed because it can affect the degree of public health. The main purpose of food safety is to prevent foods from being contaminated by foreign substances, both physical, biological, and chemical so as to reduce the potential for food hazards. One method of implementing food safety on an industrial scale is by controlling the manufacturing process through a food safety management system in the form of implementing Good Manufacturing Practices (GMP). In Indonesia, GMP for the food industry are regulated in the Regulation of the Minister of Industry of the Republic of Indonesia Number 75/M-IND/PER/7/2010. This study aims to evaluate the implementation of GMP in CV “XYZ”. The research method used is observation and interviews of 18 aspects of GMP which are applied in CV “XYZ”. The results showed that of the 136 total sub-aspects of GMP implementation that were observed, 101 sub-aspects were suitable and 35 sub-aspects were not. The percentage on the appropriate aspects is 74.26% and the aspects that are not appropriate are 25.74%. The lowest level of conformity is found in the following aspects: implementation of the guidelines (0%); final product (33.33%); and sanitation facilities (47.62%). These results indicate that the GMP applied by CV “XYZ” still needs to be adjusted to the applicable regulations.